2018
DOI: 10.29252/jrh.8.2.143
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between mother's socioeconomic status and child health

Abstract: Child health as one of the main indicators of economic development has been included directly in the millennium development goals. Due to the increased rate of mothers' employment and education along with children malnutrition, the effect of mothers' socioeconomic status on children's health was examined in this study. In case study, data on children at birth were gathered from health care records in 10 health centers of Tehran. The sample size of 400 was determined using the Cochran formula with an error marg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 13 publications
(18 reference statements)
0
3
0
Order By: Relevance
“…The chi-square statistic was 259, which showed that the total variables of the models are statistically significant differences from 0 and are significant. Given that the estimation of the selection equations was conducted based on the bivariate probit method, the coefficients obtained in these two equations are only suitable for examining the direction of effects (22,23). The marginal effects were used to examine the a Source: Author's findings effect of each of the independent variables on the probability of health insurance purchasing and purchasing from the health market, the results of which were presented in the sixth column of Table 2.…”
Section: Resultsmentioning
confidence: 99%
“…The chi-square statistic was 259, which showed that the total variables of the models are statistically significant differences from 0 and are significant. Given that the estimation of the selection equations was conducted based on the bivariate probit method, the coefficients obtained in these two equations are only suitable for examining the direction of effects (22,23). The marginal effects were used to examine the a Source: Author's findings effect of each of the independent variables on the probability of health insurance purchasing and purchasing from the health market, the results of which were presented in the sixth column of Table 2.…”
Section: Resultsmentioning
confidence: 99%
“…However, in some countries, mothers' employment tends to increase undernutrition in under-fives [43,44]. The working status of mothers negatively influenced undernutrition of their children, implying that the more chances mothers had to work, the lower the rates of undernutrition [45]; however, according to many other scholars, mothers' working and employment conditions implied diversion of time from children to work such that so that time to care for young children is reduced hence increasing the likelihood of being undernourished [46].…”
Section: Discussion Of the Resultsmentioning
confidence: 99%
“…The first 14 weeks of life are very important for an infant’s health because, during this period, infants begin to make neural connections and recognize sound and smell ( 2 ). Therefore, the child's health during this period will have a significant role in the physical, mental, and social functioning of the child in the future ( 3 ). Among the factors affecting children's health, the role of socioeconomic factors is more than 50%, which highlights the need to provide favorable economic and social factors for the family and especially for the mother in the first months of childbirth.…”
Section: Introductionmentioning
confidence: 99%